Parasitism of spores of the vesicular-arbuscular mycorrhizal fungus, Glomus dimorphicum - Boyetchko, S.M.; Tewari, J.P. (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ)l, 1991)
Spores of Glomus dimorphicum were examined for parasitism. Light and scanning electron microscopy revealed perforations, approximately 0.25 to 1.0 µm in diameter, in the spore wall. The presence of papillae, a dynamic host response, suggested that the parasitism occurred while the vesicular-arbuscular mycorrhizal fungus was still alive. No filamentous structures were detected in the spores; however, cysts of amoeba-like organisms were found in the spores and were also observed on agar plates on which surface-sterilized spores of G. dimorphicum containing such organisms were placed. It is postulated that an amoeba-like organism was the parasite, since the perforations on the spore wall were minute and no bacteria or fungi were seen inside the spores.